2016
DOI: 10.5114/hpr.2016.59590
|View full text |Cite
|
Sign up to set email alerts
|

Forced migration and sexual abuse: experience of Congolese adolescent girls in Kigeme refugee camp, Rwanda

Abstract: <b>Background</b><br /> This study deals with the link between forced migration and sexual abuse, with a special focus on adolescent girls. Existing literature associates forced migration with sexual abuse and identifies adolescent girls as the most vulnerable. However, little is known about the situation of sexual abuse among Congolese refugees in Rwanda since their arrival in 2012 due to the conflict between Congolese government forces and the M23 rebel group. This study was initiated to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 4 publications
3
22
0
Order By: Relevance
“…Adolescents and youth form the majority of these refugees. Previous research among refugee youth has documented sexual and reproductive health and rights challenges faced by teenage girls (Iyakaremye & Mukagatare, 2016;Williams et al, 2018), similar to those I found among Burundian teenagers in Mahama refugee camp in Rwanda. But to my knowledge there is no similar study focusing on pregnancy among Burundian teenagers in Mahama refugee camp.…”
Section: Current Studysupporting
confidence: 79%
“…Adolescents and youth form the majority of these refugees. Previous research among refugee youth has documented sexual and reproductive health and rights challenges faced by teenage girls (Iyakaremye & Mukagatare, 2016;Williams et al, 2018), similar to those I found among Burundian teenagers in Mahama refugee camp in Rwanda. But to my knowledge there is no similar study focusing on pregnancy among Burundian teenagers in Mahama refugee camp.…”
Section: Current Studysupporting
confidence: 79%
“…Adolescent girls also reported cases of forced and transactional sexual intercourse. Such cases were also described by Iyakaremye et al, 2016 in their qualitative findings in a refugee camp in Rwanda [31]. The proportion in our study was higher - 36.6% forced intercourse and 23.4% transactional intercourse among sexually active girls, than that reported in the study by Harrison et al, 2006 performed in Uganda – 5 and 10% accordingly [22].…”
Section: Discussionsupporting
confidence: 65%
“…From 960 records, 15 studies met the inclusion criteria. They were conducted in nine African countries which included Uganda, Ethiopia, DR Congo, Somalia, Kenya, Nigeria, Djibouti, Rwanda and Sierra Leone [ 6 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. These consisted of eight applied qualitative, five quantitative and two mixed-method study designs.…”
Section: Resultsmentioning
confidence: 99%
“…Adolescent girls in humanitarian settings experience increased exposure to early and forced marriage, coerced sex and early childbearing, as well as increased risk-taking associated with gender roles in family circles [ 5 ]. The girls in refugee camps are also vulnerable to sexual exploitation and trafficking [ 6 ].…”
Section: Introductionmentioning
confidence: 99%